A community-based programme to improve the well-being of people with mental illness and their families in a rural setting - Matsea, T.C. (North-West University, 2018)
Mental illness is a universal challenge. People with mental illness and their families often experience several challenges related to dealing with mental illness. Community-based programmes appear to be an effective approach that can facilitate reintegration of the patient into the community, empower people with mental illness and reduce the burden of care in families. The overall aim of this study was to develop a framework for a community-based programme for people with mental illness and their families in rural settings. The specific research questions were:  How do health care professionals perceive the mental health services they render to people with mental illness and their families in rural settings?  How do people with mental illness and their families in rural settings cope with mental illness?  What role do different stakeholders in rural settings currently play with regard to mental illness?  What can be done to guide social workers to develop and implement community-based programmes to improve the well-being of PWMI and their families in rural settings? The thesis consists of the following five sections:  Section A: Orientation and methodological overview  Section B: The journal articles  Section C: Conclusions and recommendations  Section D: Annexures  Section E: Consolidated reference list The primary results of the research are presented in the form of four articles intended for scientific journals. These are contained in Section B. Each article focuses on a specific goal and the research methodology which was utilised, in order to achieve the overall goal of the development of a community-based programme for people with mental illness and their families in a rural setting. The results and the nature of the results achieved with each article are covered briefly below. Article 1: The first article covers the results of a survey that was intended to assess the mental health services that are rendered by health care professionals in a rural setting. The assessment was based on the comprehensiveness, accessibility, service coverage, continuity of care, quality, person-centeredness, care coordination as well as accountability and effectiveness of the service, which are the eight attributes of good mental health service delivery. Data were sourced through a self-administered questionnaire with health care professionals from four health establishments that render mental health services to people of Mashashane. The health care professionals comprised doctors, nurses, occupational therapists, psychologists and social workers. Quantitative and qualitative data analyses were adopted. The results suggested that, of the eight attributes, only comprehensiveness was positively perceived. The study revealed that lack of resources is the major obstacle to the delivery of mental health services, while lack of training is also a contributing factor to the provision of ineffective mental health service. These results depict the inadequacy of mental health services, hence their inability to improve the well-being of people with mental illness and their families. The results contributed to the development of a framework that would guide social workers to develop and implement community-based programmes in a rural setting. Article 2 focuses on the results of an investigation of the coping strategies adopted by people with mental illness and their families living in the selected rural setting. The data was collected through semi-structured interviews with 20 participants (10 people with mental illness and 10 family members considered primary caregivers) who met a predetermined set of criteria. The results show that participants’ understanding of mental illness is based on their belief systems, values and perceptions about the cause of mental illness. Culture seemed to influence perceived causes of illness. Mental illness has a social, emotional and financial impact on all participants, whereas only people with mental illness reported experiencing any physical health impact caused by the side effects of the treatment. The study revealed that participants received inadequate support from both formal and informal systems. As a result, they rely on one another to cope with challenges posed by mental illness. Participants were found to have adopted both adaptive and maladaptive strategies in order to cope. A community-based programme was recommended as a strategy that could improve participants’ well-being. The views of stakeholders of their role as a support system of people with mental illness and their families are covered in Article 3. The data was generated via the use of focus group discussions with various stakeholders. These stakeholders were traditional leaders, traditional health practitioners, church members, police officers and home-based care groups. A total of seven focus group discussions were conducted with a minimum of five and a maximum of eight participants respectively. The study revealed that stakeholders based their understanding of mental illness on how other people should react towards people with mental illness, the cause of mental illness and the unusual behaviour displayed by people with mental illness. Witchcraft seemed to be the predominant perceived cause of mental illness. Stakeholders acknowledged the availability of both formal and informal systems but viewed them as ineffective in terms of providing support to people with mental illness and their families. Fear and lack of skills on how to cope with people with mental illness were found to be the main factors that prevent stakeholders from providing adequate support. Collaboration was identified as a suitable mechanism for improved mental health service delivery, provided a third party intervenes to facilitate the process. These findings and those of Articles 1 and 2 contributed to the formulation of recommended guidelines for stakeholders and health care professionals to provide support to people with mental illness and their families. Article 4 focused on the development of a community-based framework. The results obtained via the empirical studies (see articles 1 to 3), combined with a literature study, were used to develop a framework for a community-based programme for people with mental illness and their families. A six-module educational programme was developed as an intervention aimed at people with mental illness and their families. Secondly, guidelines to improve support for people with mental illness and their families were formulated as an intervention aimed at health care professionals and stakeholders. These interventions were validated to assess content suitability and usefulness for the context. The results indicated the appropriateness and usefulness of the framework in the rural context. A seven-step framework that can be used by social workers to develop and implement community-based programmes in rural settings, was proposed. This framework outlines important aspects for consideration during the development and implementation processes.
PhD (Social Work), North-West University, Potchefstroom Campus
Keywords: Community-based programme; mental health; mental illness; rural setting; well-being; families